2007
DOI: 10.1038/sj.gene.6364391
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the pre-BCR complex in a large cohort of patients affected by autosomal-recessive agammaglobulinemia

Abstract: Autosomal-recessive agammaglobulinemia is a rare and heterogeneous disorder, characterized by early-onset infections, profound hypogammaglobulinemia of all immunoglobulin isotypes and absence of circulating B lymphocytes. To investigate the molecular basis of the disease, 23 patients with early-onset disease and no mutations in Bruton tyrosine kinase, the gene responsible for X-linked agammaglobulinemia, were selected and analyzed by direct sequencing of candidate genes. Two novel mutations in the m heavy chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…This mutation has occurred on at least three different Ig haplotypes, indicating that this is a hot spot for mutations. The study indicated that at least 20-30% of patients with autosomal recessive defects in B cell development have mutations in the l heavy chain and multiple additional patients have recently been described [16][17][18].…”
Section: Defects In Early B Cell Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…This mutation has occurred on at least three different Ig haplotypes, indicating that this is a hot spot for mutations. The study indicated that at least 20-30% of patients with autosomal recessive defects in B cell development have mutations in the l heavy chain and multiple additional patients have recently been described [16][17][18].…”
Section: Defects In Early B Cell Developmentmentioning
confidence: 99%
“…Interestingly, in one of the latter studies [16], two patients with compound heterozygous variations in the pre-B lymphocyte gene 1 (VpreB1) were also described. Although it cannot be ruled out that these variations represent low-frequency polymorphisms, they may be the first cases suggesting that VpreB mutations are indeed involved in the etiology of agammaglobulinemia in humans.…”
Section: Defects In Early B Cell Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Autosomal recessive agammaglobulinemia represents 5% of all patients with agammaglobulinemia [2,3]. In 20% to 30% of this small patient group, mutations in the gene for the μ heavy-chain gene are found [4].…”
mentioning
confidence: 99%
“…Abnormal laboratory parameters include low Ig levels and low or absent peripheral blood mature B lymphocytes [5] [9]. For determine the genetic defect and to confirm the diagnosis, should be performed molecular genetic testing.…”
Section: Introductionmentioning
confidence: 99%